Sensitive periods in human ontogenesis - Kabanov, Yu. M.; Venskovich, D. A.; Trushchenko, V. V.; Koloshkina, V. A. (Theory and Practice of Physical Culture, 2019)
The article highlights the issues related to the development of man`s motor abilities during ontogenesis. The authors carried out a theoretical analysis of the data obtained by Belarusian and Russian scientists in the field of theory and methodology of physical culture, devoted to the study of the signs of the sensitive periods of development of man`s motor abilities. The analysis revealed that, at seven, the number of sensitive periods of development of motor abilities in both males and females increases; moreover, their number in females exceeds that in males, and this dynamics remains unchanged until the age of 11 in females and 12 - in males. At the age of 11, the number of signs of the sensitive periods in females reaches its maximum, after which it decreases significantly up to 13 years of age, which may be due to puberty. Males aged from 10 to 12 have a wavy dynamics in the quantitative signs of the sensitive periods, but it is weakly pronounced. In the period from 12 to 14 years, representatives of both sexes have the same number of signs of the sensitive periods. From 13 to 14, females and males are observed to have another increase in their number. Moreover, starting from 15, these indicators in males begin to exceed those in females. From the age of 14, there is a gradual decrease in the number of sensitive periods in representatives of both sexes. This dynamics will persist over subsequent age periods up to 22 years.